Optimization of ultrasound‐assisted extraction of cold‐brewed black tea using response surface methodology. (16th September 2020) - Raghunath, Sonali; Mallikarjunan, Kumar
Abstract: Black tea is considered as good source of bioactives like phenolics and antioxidants. In this study, cold brewing of black tea is coupled in combination with ultrasound‐assisted extraction (UAE) to maximize extraction efficiency of bioactives. Response surface methodology was designed to optimize the conditions for extraction using UAE for cold‐brewed black tea. A multiparameter face‐centered central composite design was used to predict the conditions (amplitude: 10–70%, solvent volume: 25–100 ml, and sonication time: 10–60 min). The results obtained indicated a second‐order polynomial model. The optimized conditions for maximum extraction of bioactive for cold brewing of black tea were found to be 69.9% amplitude, 25 ml solvent volume, and 30 min of sonication time. The experimental values from the optimal process were as follows: 72.2 mg gallic acid equivalent (GAE)/g, 6.77 mg GAE/g, 37.67%, 62.97% for total phenolic content (TPC), total tannin content, 2, 2‐diphenyl‐1‐picrylhydrazyl, and 2, 2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid). The validation results agreed with the predicted models and showed an increase of 4 folds for TPC and 1.5 folds increase in antioxidant activity of cold‐brewed black tea. The displayed outcomes can remain as an extension for designing techniques for the accelerated extraction process for cold‐brewed black tea. Practical Application: The application of cold brewing is limited due to the low extraction efficiency and longer extraction time. Ultrasound‐assisted extraction (UAE) improves the extraction of valuable nutrients with higher efficiency and shorter extraction time, helping the industry to produce larger amounts of cold‐brewed tea with lesser time. For other researchers, UAE‐treated cold‐brewed tea is a technique, which yields higher antioxidants and can be used as a method to study other cold‐brewed teas in the market. Abstract : RSM Modeling of ultrasound‐assisted cold‐brewed tea.